Spectroscopic impact on protein and carbohydrate inherent molecular structures of barley, oat and corn combined with wheat DDGS. Issue 4 (2011) - Abeysekara Abeysekara, S. S.; Damiran Damiran, D. D.; Yu Yu, P. P.
Abstract : The objectives of this experiment were to use non-invasive and non-destructive infrared molecular spectroscopy as a novel approach to explore and identify protein and carbohydrate molecular structure spectral features of DDGS (dried distillers grain solubles from wheat, Triticum aestivum ) and its combinations with barley ( Hordeum vulgare ), corn ( Zea mays ) and oat ( Avena sativa ). The spectral parameters assessed in this study included amides, protein molecular structures of α -helix and β -sheet, lignin, cellulosic compounds (CeC) and nonstructural carbohydrates (NSC). The results of the study show that the combinations of DDGS with cereal grains significantly changed ( P < 0.05) protein and carbohydrate structures and protein secondary structure. The use of FT/IR molecular spectroscopy in terms of identification of inherent structural changes was remarkable. The combination of DGGS with different grains alters the constituents and intrinsic molecular structures. This change would improve the nutritional quality and digestive characteristics of the feed. Further studies are recommended to evaluate the effect on digestibility, availability and its structural correlation.